THE EFFECT OF ASSET STRUCTURE ON DEBT TO EQUITY RATIO ON REGISTERED AUTOMOTIVE COMPANIES - Muhammad Firza Alpi (CERED Indonesia Institute, 2020)
This research is intended to find out and analyze the influence of Asset Structure, on Debt to Equity Ratio on Automotive companies registered with IDX. This research approach uses associative shortness. The object of this research is automotive companies listed on the Indonesia Stock Exchange (IDX) period 2013-2017. The population used is 12 companies, the method of determining the number of samples in this research is purposive sample and selected as a sample of 9 companies. The data collection technique used is a documentation study. Data analysis techniques in this research are multiple linear regression methods and determination coefficients, which in this study used the SPSS 16.00 program. The results showed that Asset Structure had no significant effect on the Debt to Equity Ratio on Automotive companies listed on IDX for the period 2013-2017.